New Deal Radio The Educational Radio Project. - Goodman, David (Rutgers University Press, 2022)
"New Deal Radio examines the federal government's involvement in broadcasting during the New Deal period, looking at the U.S. Office of Education's Educational Radio Project. The fact that the United States never developed a national public broadcaster, has remained a central problem of US broadcasting history. Rather than ponder what might have been, authors Joy Hayes and David Goodman look at what did happen. There was in fact a great deal of government involvement in broadcasting in the US before 1945 at local, state, and federal levels. Among the federal agencies on the air were the Department of Agriculture, the National Park Service, the Works Progress Administration (WPA) and the Federal Theatre Project. Contextualizing the different series aired by the Educational Radio Project as part of a unified project about radio and citizenship is crucial to understanding them. New Deal Radio argues that this distinctive government commercial partnership amounted to a critical intervention in US broadcasting and an important chapter in the evolution of public radio in America"--